Menggali Pengalaman Penggunaan Aplikasi Canva dalam Meningkatkan Pemahaman Siswa SD terhadap Mata Pelajaran IPS - Amedoma, Divana; Azmi, Nur Kholila; Alwi, Nur Azmi; Adrias, Adrias (TSAQOFAH, 2024)
This research investigates the use of the Canva application in improving students' understanding of Social Sciences in Elementary Schools. By using a descriptive qualitative approach, this study will involve classroom observations, as well as literature studies regarding students using Canva. The research results also show that Canva is effective in facilitating students' understanding of several social studies concepts through creative visualization. Students may also respond positively to using Canva, which indicates increased motivation and engagement in learning. However, there are challenges related to digital skills and access to technology. The implications of this research will at least highlight the importance of ongoing training for teachers and adequate technical support to optimize the use of Canva in primary education.